Crop‐associated virus infection in a native perennial grass: reduction in plant fitness and dynamic patterns of virus detection. (16th January 2017) - Alexander, Helen M.; Bruns, Emily; Schebor, Hayley; Malmstrom, Carolyn M.
Summary: To understand the eco‐evolutionary significance of plant viruses in nature, we must (i) quantify the effects of infection on plant fitness and (ii) recognize that native plants are increasingly exposed to crop‐associated viruses. Studies of perennials are particularly needed: most of our knowledge of plant‐virus interactions is from annuals, yet long‐lived species dominate landscapes. Here we used aster models for life‐history analysis and longitudinal measures of plant virus status to evaluate multi‐year consequences of crop virus infection in a native perennial. We used Barley yellow dwarf virus acquired from wheat to inoculate seedlings of Panicum virgatum L. (switchgrass), a North American prairie grass. We grew inoculated and mock‐inoculated individuals of two ecotypes for 3 years in the field. We measured plant size, infection status and fitness components. Aster modelling provided integrated multi‐year measures of fitness. Crop virus inoculation reduced multi‐year native plant fitness by 30% over 2 years despite generally asymptomatic infection and evidence of resistance. This reduction was greater than predicted from individual fitness components or most size measures. Ecotypes differed in response, with the lowland ecotype experiencing higher apparent recovery from infection. Virus treatment in the upland ecotype delayed flowering phenology and reduced seed filling. Synthesis . Our use of field experimentation, surveys of plant infection status and aster modelling demonstrates a rigorous and broadly applicable approach for quantifying the effects of viruses and other microbes on multi‐year plant fitness. We found that a crop virus had negative multi‐year effects on native plant fitness even after infection was no longer detected. Viruses may have substantial effects on native vegetation with domestication of landscapes and agricultural expansion. Abstract : Field experimentation, surveys of plant infection status and aster modelling provide a rigorous and broadly applicable approach for quantifying the effects of microbes on multi‐year plant fitness. We found that a crop virus had negative multi‐year effects on native plant fitness even after infection was no longer detected. Viruses may have substantial effects on native vegetation with agricultural expansion.